Yield projection using productive variables and various types of banana (Musa spp.) seed in Turbo-Colombia. (2022)
The productivity of banana cultivation is influenced by different physical, chemical and biological factors, which, in turn, vary between lots, farms and geographical areas; added to this the high climatic variability, high cost of inputs, decrease in labor and adjustment to the supply-demand of the finished product forces the producer to optimize resources and carry out interventions to schedule harvests. The objective of this research was to make a performance projection, considering production variables. The study was carried out during the second half of 2021 and first quarter of 2022 in the department of Antioquia, municipality of Turbo, for the projection was taken into account seed type, weeks to harvest, cluster weight, population, return, collection and loss. Possible scenarios are presented with their respective interactions and performance response. The experimental design was in completely random blocks with 3 repetitions, the data were analyzed with R Studio 2022.02 software, non-parametric tests (Kruskal-Wallis; Yuen) and comparison of means with a post-analysisKruskal-Wallis with a 95% confidence level. Significant differences were found (P<9e-5), where the treatment of corm + pseudostem was the one that presented the best indicators with a number of weeks accumulated at harvest of 28.40±0.35 and a cluster weight of 24.3±0.19 kg.